Relationship between macular pigment and visual function in subjects with early age-related macular degeneration. Issue 2 (18th April 2016) - Akuffo, Kwadwo Owusu; Nolan, John M; Peto, Tunde; Stack, Jim; Leung, Irene; Corcoran, Laura; Beatty, Stephen
Abstract : Purpose: To investigate the relationship between macular pigment (MP) and visual function in subjects with early age-related macular degeneration (AMD). Methods: 121 subjects with early AMD enrolled as part of the Central Retinal Enrichment Supplementation Trial (CREST; ISRCTN13894787 ) were assessed using a range of psychophysical measures of visual function, including best corrected visual acuity (BCVA), letter contrast sensitivity (CS), mesopic and photopic CS, mesopic and photopic glare disability (GD), photostress recovery time (PRT), reading performance and subjective visual function, using the National Eye Institute Visual Function Questionnaire-25 (NEI VFQ-25). MP was measured using customised heterochromatic flicker photometry. Results: Letter CS, mesopic and photopic CS, photopic GD and mean reading speed were each significantly (p<0.05) associated with MP across a range of retinal eccentricities, and these statistically significant relationships persisted after controlling for age, sex and cataract grade. BCVA, NEI VFQ-25 score, PRT and mesopic GD were unrelated to MP after controlling for age, sex and cataract grade (p>0.05, for all). Conclusions: MP relates positively to many measures of visual function in unsupplemented subjects with early AMD. The CREST trial will investigate whether enrichment of MP influences visual function among those afflicted with this condition. Trial registration number: ISRCTN13894787.